Correlation of TNF-α with Systemic Lupus Erythematosus Activity in Mohammad Hoesin Hospital Palembang - Ismed, Yonis; Kurniati, Nova; Theodorus; Yuniza; Salim, Eddy Mart (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Systemic lupus erythematosus (SLE) is a persistent autoimmune disorder marked by immunological dysregulation and widespread inflammation. Tumor necrosis factor-α (TNF-α), a pivotal pro-inflammatory cytokine, has been associated with the pathophysiology of systemic lupus erythematosus (SLE), although its clinical relevance is still debated. This study aims to assess the connection between serum TNF-α levels and disease activity, as quantified by the Mexican Systemic Lupus Erythematosus Disease Activity Index (MEX-SLEDAI), in Indonesian patients with systemic lupus erythematosus (SLE). A cross-sectional study was performed including 34 patients exhibiting mild-to-moderate systemic lupus erythematosus activity (MEX-SLEDAI ≤12) at Dr. Mohammad Hoesin General Hospital in Palembang, Indonesia. Individuals with significant active disease were excluded. Serum TNF-α concentrations were quantified via a commercial ELISA kit, while disease activity was evaluated through MEX-SLEDAI. Correlation analysis was conducted using Spearman’s rank test, with p < 0.05 being statistically significant. The average age of participants was 33.6 ± 11.0 years, with 94.1% identifying as female. The median MEX-SLEDAI score was 3 (range 2–7), and the median TNF-α level was 1.834 pg/mL (range 0.99–8.62). No substantial connection was detected between serum TNF-α levels and disease activity (r = 0.111, p = 0.533). This suggests that serum TNF-α levels did not correlate with or forecast clinical disease activity in this investigation. The results indicate that the efficacy of TNF-α as a biomarker in SLE may be contingent upon contextual factors, especially illness severity. Additional multicenter and longitudinal studies involving individuals with a broader spectrum of disease activity are necessary to elucidate its clinical significance.